KETEPATAN PEMBERIAN DIET DENGAN PENGETAHUAN PRAMUSAJI TERHADAP MUTU PELAYANAN INSTALASI GIZI RSUD LEUWILIANG - Rini Suryanti; Sarah Handayani (JURNAL BIDANG ILMU KESEHATAN, 2023)
Background : RSUD Leuwiliang has 391 inpatient beds that servers must feed. The results of the accuracy of data on the accuracy of patient feeding at the Nutrition Installation of Leuwiliang Hospital in 2018 were 98.25%, 98.45% in 2019, 98.42% in 2020, and 98.80% in 2021. The indicators show that An error has occurred in administering the patient's diet. RSUD Leuwiliang has not yet achieved a minimum service standard of 100% for indicators of the accuracy of patient feeding. Based on the background above, the researcher will know more about the results of "Accuracy in providing a diet with the knowledge of the waiter on the quality of nutrition service at Leuwiliang Hospital." Objective : I am measuring the knowledge and thoroughness of the waiter in providing food according to the patient's diet on the quality of nutrition installation services. Methods : This descriptive-analytic study uses a cross-sectional study design and a closed quantitative approach. Primary data was taken using a questionnaire with the total sample method used to test the knowledge of servers with the accuracy of giving a diet—quantitative approach using univariate analysis and bivariate analysis. Results : The accuracy of giving the diet at Leuwiliang Hospital is based on the questionnaire results in table 3. Poor knowledge is 36%, those who do the diet incorrectly are 12%, and those who carry out the diet properly are 24%, while 64% with good knowledge, there is no frequency of dietary values. Inappropriate, and 64% carry out the diet correctly. Compared with the Minimum Service Standards, where the indicator for the accuracy of the diet must be 100%, the results showed that the minimum service standard assessment had not been met, so the conclusion of the final statistical analysis using the Chi-Square test (X2) resulted in a P-Value = 0.014